Technological Gaps Among Fishermen Operating Motorised and Non-motorised Fishing Crafts - Mohan, Braj; S., Balasubramaniam; M.K., Kandoran (Fishery Technology, 2025)
This study was conducted in six districts of Kerala state to monitor the technological gaps among fishermen. Among the fishermen operating motorised fishing crafts, the technological gap was wider among those operating plankbuilt crafts (34.65%). The catamaran operators had wider technologic! gap (45.60%) among the non-motorised categories. Out of 18 independent variables, three variables viz, the size of craft operated, number of nets used and mass media exposure were found to be key variables among fishermen operating non-motorised crafts. In the regression analyses, the R2 values were found to be high and significant among all the categories. The fishing craft-gear combinations used by different categories of fishermen were recorded.